Economic Policy Uncertainty and the Co-Movement between REITs and Exchange Rate - Raheem, Ibrahim; Fasanya, Ismail; Yusuf, Agboola (Review of Economic Analysis, 2022)
The REITs market has attracted a lot of interest among the academic, policymakers, and market participants. The linkages between REITs and macroeconomic and financial variables have been adequately explored in the literature, with more emphasis on linear models. This study expands the frontier of knowledge by examining the role of uncertainty in the comovement/spillover between REITs and the currency markets. Some interesting results were observed. First, using the Diebold and Yilmaz (2012) spillover test, we find that there is strong connectedness between the REITs and currency markets. Second, the BDS test shows that nonlinearity is a very crucial factor to be put into consideration when examining the role of EPU in affecting the interactions between REITs and exchange rate markets. Third, the non-parametric causality-in-quantile test confirms that the connectedness between the markets and EPU is stronger around the lower and middle quantiles. These results have important policy implications for policymakers and market participants. The study also offers suggestions for future research.